The protective role of muscone in the development of COPD - Feng, Tiantian; Guo, Xiaolong; Chen, Wei; Zhang, Yanying; Dai, Runjing; Zhang, Yinfang; Liu, Yongqi; Liu, Yiya; Song, Peng; Fan, Jingchun (Frontiers in Immunology, 2025)
BackgroundMuscone, a key component of musk, exhibits anti-inflammatory properties. However, its therapeutic potential in inflammatory lung diseases, such as chronic obstructive pulmonary disease (COPD), remains largely unexplored. This study aimed to investigate whether Muscone could exert a protective effect in a mouse model of COPD in vivo.MethodsA COPD animal model was established by exposing mice to cigarette smoke (CS) and administering lipopolysaccharide (LPS) intranasally. After 4 weeks, mice were treated daily with dexamethasone (DEX) or different doses of Muscone for 3 weeks. Mouse body weight, lung function, and histopathology were determined. Serum levels of cytokines (IL-38, IL-1β, IL-17, TGF-β, IFN-γ) were measured using ELISA and qRT-PCR. Lung expression of CXCR3, IFN-γ, IL-17A, and RORγt was assessed by immunofluorescence.ResultsThe body weight of COPD mice was significantly lower than that of Muscone-treated COPD mice, consistent with decreased lung function, accompanied by reduced circulating and lung IL-38 levels. After Muscone administration, lung function was significantly improved, accompanied by upregulation of circulating and lung anti-inflammatory cytokines, including IL-38, in a dose-dependent manner, while the expression of pro-inflammatory cytokines was significantly reduced. Additionally, Muscone significantly inhibited the protein expression of CXCR3, IFN-γ, IL-17A, and RORγt in lung tissues of COPD mice.ConclusionThis study demonstrates that Muscone improves lung function in mice with COPD, potentially through a mechanism that may involve the modulation of cytokine expression, including the potential upregulation of anti-inflammatory cytokines such as IL-38. The precise underlying mechanisms of Muscone’s therapeutic effects in COPD remain to be fully elucidated. Further research is needed to investigate the correlation between COPD lung pathophysiology and the specific effects of Muscone treatment, including a more detailed analysis of the balance between pro- and anti-inflammatory mediators in COPD animal models, particularly utilizing IL-38 GKO mice to further investigate the role of IL-38 in mediating the therapeutic effects of Muscone.